PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING UNTUK MENINGKATKAN HASIL PEMBELAJARAN PADA MATERI MICROSOFT EXCEL 2007 MATA PELAJARAN TIK KELAS XI SEMESETER 2 DI MADRASAH ALIYAH SMIP 1946 BANJARMASIN TAHUN PELAJARAN 2016/2017 - arief, Karlianor (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2018)
The problem is the low of student?s achievement. This study aims to determine the improvement of learning outcomes and student activities through STAD type cooperative learning model on the subject matter introduction of Microsoft Excel 2007 program subjects ICT students class XI semester. This research used Class Action Research method (PTK). This classroom action research is divided into three cycles, each cycle encompassing planning, action, observation, and reflection activities. The place of research is in Madrasah Aliyah SMIP 1946 Banjarmasin, which was held on January 13, 2016 until the date of March 10, 2017 semester Even academic year 2016/2017. The subjects of the study were the students of class XI IPS Madrasah Aliyah SMIP 1946 Banjarmasin on the subject of Communication Technology and Informasin (ICT). The result showed that learning with STAD type cooperative model can improve learning achievement and student activity on the subject matter of introduction of Microsoft Excel 2007 program of ICT Class XI semester 2. The improvement of this learning achievement can be seen in the first cycle with the percentage of complete students of 78.26%, cycle II with the percentage of students completed by 82.61%, and cycle III with the percentage of students who complete 95.65%. Student learning activity on cycle I with average amount 73,00%, cycle II with average amount 85,00% and in cycle III with average amount 92,00%.